PENGELOLAAN EKOSISTEM PESISIR - Yowan Tamu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2017)
The demage of coastal ecosystem it’s a configuration character or behavior human in curious toward system ecological order. Therefore, coastal acosystem management obviously to do in an integration manner. Especially involve character education since based school ages. In this case, character education in the IPA learning. This matter to do because IPA learning have an improve multiple competition who are needful educate participant to directly involved in the coastal ecosystem management through an understating of ecosystem concept and an environmentaly sound along with have care character about an environment. The grounded in this review so this research on a long term intent in make an understating of ecosystem concept in a contextual manner and socio-cultural value charged which is afterwards expected of could shaping educate participant character toward nature and the environment. In particular, this research intent to developing coastal ecosystem learning character in the based school coastal region socio-cultural approach.